Study on the Seismic Performance of Small-Diameter Bolts Reinforced in Grottoes - Ningbo Peng; Bo Sun; Jizhong Huang; Yun Dong; Ye Zhu (Advances in Civil Engineering)
The Yungang Grottoes, a World Heritage Site in Datong, consist of 252 caves that are noted for their collection of 5th- and 6th-century Buddhist grotto sculptures and reliefs. Various diseases have appeared in the grottoes under the general influence of natural and artificial factors. Bolt support is a commonly employed method for grotto reinforcement and has been widely applied in many projects. Small-diameter bolts have also been used in the reinforcement projects at the Yungang Grottoes, but the corresponding effect on the seismic performance of grottoes is still unclear. In this paper, a dynamic analysis via the numerical modelling of an ear grotto of the 19th grotto in Yungang is established, and the rock displacement, acceleration, and bolt axial force responses under a seismic wave are analyzed. The results show that the seismic dynamic responses of grottoes are greatly affected by the cliff structure. The displacement and acceleration responses of the cliff body vary greatly within the abrupt transition of the cliff structure. Based on this variation, the seismic capacity of small-diameter bolts in the vertical direction is greater than that in the horizontal direction. The axial force of a bolt is small at both ends of the bolt, large in the middle of the bolt, small on the top of a cliff, and large at the bottom of the cliff. Although the axial force is small, the upper rock mass of the grotto has a tendency to undergo relative movement compared with the outer rock mass. The results also indicate that based on the structural defects in the vertical direction of the cliff body caused by grotto excavation, the inclined angle of the bolt should be increased as far as possible or vertical support should be adopted to enhance the stability of the rock mass at the top of the grotto.